Kepuasan pasien di jakarta barat terhadap gtsl nilon termoplastik - Wirahadikusumah, Andy; Funny Setioningrum, Dominica (Fakultas Kedokteran Gigi Universitas Trisakti, 2023)
disorders, and aesthetic function. Partial tooth loss can be overcome by using removable partial dentures (RPD). There are various types of removable partial dentures, one of which is made of thermoplastic nylon. Objectives: To describe patient satisfaction using thermoplastic nylon-based removable partial dentures in West Jakarta. Materials and Methods: a descriptive observational study using a cross-sectional method. 109 Respondent participated in this study. A Validated quesionnaire containing 20 questions was given via Google forms to measure patient satisfaction. Results: 20 questions that have passed the validity and reliability tests, the results show that the age group that uses the most nylon thermoplastic RPD is 36-45 years (42.2%). There were more female respondents than female respondents (67.49%). Most of the denture use time is less than 1 year (56%). The highest distribution of tooth loss was a combination of anterior and posterior teeth (42.2%), front of the maxilla (23.9%), back of the mandible (21.1%), back of the maxilla (11.9) and the least was the front of the mandible (0.9%) ). As many as (1.8%) were dissatisfied, 12.8% were satisfied, and 85.3% were very satisfied with their thermoplastic nylon removable partial denture. Conclusion: 93 respondents were very satisfied with their thermoplastic nylon removable partial dentures.